Complement, natural antibodies, autoantibodies and tissue injury - Fleming, Sherry D.; Tsokos, George C. (My University, 2013)
Activation of the classical complement pathway represents an effector mechanism of intestinal ischemia/reperfusion injury. Mice deficient in complement receptors 1 and 2 fail to produce a component of the natural antibody repertoire that binds to ischemia-conditioned tissues and activate complement. In contrast, mice prone to autoimmunity display accelerated and enhanced tissue injury that results from the binding of autoantibodies to injured tissues. Our experiments demonstrate that naturally occurring antibodies and autoantibodies mediate tissue injury only after an organ has been subjected to a stressor such as ischemia.
Keywords: Natural antibodies; Tissue injury; Autoantibodies; Complement activation